PERSONIFICATION TRANSLATION STRATEGY IN ANDREA HIRATA’S NOVEL LASKAR PELANGI INTO ENGLISH - Mochammad Fiko Ferdiansyah; Dimas Adika (STKIP Paracendekia NW Sumbawa, 2026)
This study aims to identify the forms of personification used in Andrea Hirata’s Laskar Pelangi and to explain the translation strategies applied by Angie Kilbane in its English version, The Rainbow Troops. The research employs a descriptive qualitative method by analyzing 32 instances of personification found in both texts. The analysis draws on theories of figurative language translation proposed by Newmark (1988), Larson (1998), and Baker (2018). The findings reveal several patterns of personification in the novel, including inanimate objects portrayed as performing human actions, abstract concepts given human emotions, and natural phenomena depicted as if they were alive. In the translation, the most frequently used strategy is literal translation, indicating that many personificative expressions in Indonesian can be rendered into English without major adjustments. Nevertheless, strategies such as modulation, equivalent translation, and adaptation are still necessary to maintain logical flow, naturalness, and readability for the target audience. Overall, the study emphasizes that translating literary works requires a careful balance between preserving the author’s stylistic choices and adapting the text so that it remains accessible and meaningful in another language.